Impact of a novel HPAM/GO-SiO2 nanocomposite on interfacial tension: Application for enhanced oil recovery - Lashari, N. (Taylor and Francis Ltd., 2022)
The article discusses experimental investigation of a polymeric nanocomposite composed of HPAM/GO-SiO2. The DLS, zeta potential, scanning electron microscopy, and infrared spectroscopy are utilized to analyze the resulting composite. As the interfacial tension of a nanopolymeric solution is dependent on a few critical variables, the research simulated interfacial tension using response surface methodology. The results indicate that interfacial tension is not equally critical for all parameters. There was no evidence presented to demonstrate the model's inadequacy. The central composite design had an R2 of 86.81, indicating that it was the optimal choice for evaluating the impact of hybrid polymeric nanofluids. Â© 2022 Taylor & Francis Group, LLC.